-7+2h=-15

Simple and best practice solution for -7+2h=-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7+2h=-15 equation:


Simplifying
-7 + 2h = -15

Solving
-7 + 2h = -15

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 2h = -15 + 7

Combine like terms: -7 + 7 = 0
0 + 2h = -15 + 7
2h = -15 + 7

Combine like terms: -15 + 7 = -8
2h = -8

Divide each side by '2'.
h = -4

Simplifying
h = -4

See similar equations:

| 2(4b-6)+6(-3-2b)=6-4b+4-5b | | 3x+9=-6x+16 | | 4x+6=y-3 | | 8u+1=7u+1 | | 4k-2=k-6 | | 15+.25x= | | 3(2x+1)=5(x-4) | | 5(b-6)=3(b+4) | | x+y=4x | | 3(3-x)=15x-27 | | -5y+-5(6-2y)=0 | | 15x-10=-9x+3 | | lny=-3ln(x)+ln(C) | | 4-8x-x=-23 | | 3a^2+25a+50=0 | | 8q-5=5q+3 | | 2y+y-.5=23.5 | | 11-9=-23 | | X+6*4=126 | | 8x=4x-6 | | .4x^2+.2=x | | x-6-7=26(x-7) | | -8x-x=99 | | 6n+2=n+8 | | 2(9c-6)=14 | | -4m-2=82 | | -8(n-7)+3(n-3)=41 | | (9x+y)+(3x+2y)=180 | | -8(n-7)+3(n-3)=31 | | 64=8w-8 | | 2N+7(9N+10)= | | 6+.010x=0.15x+8 |

Equations solver categories